The Spectator, 1972-04-27 - Spectator, Valdosta State University (Valdosta State University, 1972)
The Spectator, April 27, 1972. Vol. 38, Issue 24. --APATHY AT VSC? HARDLY! -- VSC Sophomore Named Miss Gum Spirits -- A Spectator For All Seasons -- Letters To The Editor -- Personal Approach Benefits Senators -- First Student Performance Slated For Whitehead -- Heavy Sounds -- FREAKS CELEBRATE -- sss HAS NEW LAWS -- King Herion Revisited -- Kappa Delta Shows Winning Tradition -- Regents Express Appreciation -- Soprano Recital Here May 4 -- VSC Coeds With New Science Of Teaching -- Greek Week Well Attended -- Tommy Thomas The Winner -- Rebs Take W. Ga. Twice -- VSC Golfers Rate With The Best -- Rebels Sign Indiana Cagers -- ACTION RAGES AS INTRAMURAL SEASON COMES TO A CLOSE ... -- History Professor Turns Biographer -- Military Ball Set For This Saturday -- SPEAKING OUT What Do You Think Is The Purpose Of The SGA??? -- ANY RIGHTS AT 18? -- Barnes Accomodates VSC Greek Organizations
The VSC Spectator
Digitized from original print, Valdosta State University, March 15, 2015.
Keywords: The Spectator; The VSC Spectator; Valdosta State College's Student Newspaper; Valdosta State College; VSC; Valdosta State University; VSU; 1970s; 1972